Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Perusahaan: Studi Pada Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2014-2018 - Nabila Azahra; Tieka Trikartika Gustyana (JRAK: Journal of Accounting Research and Computerized Accounting, 2020)
In facing the dynamic economic movements and the increase of competition between companies, each company must always be sensitive to the challenges and opportunities that exist to maintain and increase their competitive advantage. However, their lack of awareness on the importance in managing the dynamic knowledge makes them gain a minimum profit. The study was conducted to show the influence of Intellectual Capital on the Company’s Financial Performance. The use of Purposive Sampling Technique in sample selection resulted in the research samples of 8 Pharmaceutical Sub Sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The data that has been obtained is then processed using panel data regression and testing the hypotheses between the research variables both partial and simultaneous to determine the relationship. The results show that only VACA and VAHU have an influence on the company's financial performance. While simultaneously, VACA, VAHU, and STVA together affect the company's financial performance. Keywords: Return On Equity (ROE), Structural Capital Value Added (STVA), Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Value Added Intellectual Capital (VAIC)